Comparison of the characteristics of six salt crusts - Xu, Boshi; Li, Chengzhi; Li, Zhaoti (Frontiers in Environmental Science, 2022)
Salt crust is a soil layer formed by the cementation of soluble salt on the surface or inside of soil with soil particles. Salt crust can alter the soil’s ability to resist wind erosion. To explore the characteristics of different types of salt crust, six kinds of salt (CaCl2, KCl, Na2SO4, NaCl, Na2CO3, and NaHCO3) were selected and six salt content (0.2%, 0.5%, 1%, 2%, 3%, and 4%) were set up to conduct the experiment of a sandy soil crust. The experiment compares the characteristics of the crust appearance, compressive strength, and toughness of six selected kinds of salt crust. The results showed that: (1) Na2SO4 formed the subflorescence, while CaCl2, KCl, NaCl, Na2CO3, and NaHCO3 formed the efflorescences. (2) The compressive strength and the toughness of Na2SO4 salt crust initially increased and then decreased as the salt content increases, and both the strength and toughness reached the maximum when the salt content was 3%. At first, the compressive strength of NaCl crusts increased and then stabilized as a result of the increase in salt content. The toughness of the NaCl salt crust experienced an initial increase and then a decrease, reaching the maximum when the salt content was 3%. The compressive strength and toughness of the salt crusts of CaCl2 and KCl increased as the salt content increased. There was a slight increase in the compressive strength of the crusts formed by Na2CO3 and NaHCO3, with hardly any noticeable change even as the salt content increased, and the maximum compressive strength was only 0.029 MPa and 0.4 MPa, respectively. (3) The crusts of Na2CO3 and NaHCO3 were susceptible to wind erosion; while the crusts of KCl, CaCl2, NaCl, and Na2SO4, having high compressive strength, and crust toughness, were capable to resist wind erosion.